(untitled) (Asian Journal of Medical and Biological Research, 2020)
In the present study a comparative evaluation microscopic agglutination test with rLigB protein based latex agglutination test was carried out, which is a cross reacting lipoprotein able to detect acute infection caused by any pathogenic leptospiralserovars. It was employed for serodiagnosis of leptospirosis. The 46 KDa 6X His tagged LigB protein, obtained by IPTG induction of recombinant E. coli M15 cells containing the N-terminal region of LigB gee in PQE30 expression vector, was purified by Ni-NTA affinity chromatography and adsorbed on latex bead surface for performing latex agglutination test against Leptospirosis suspected wildlife field sera. A total of 80 wildlife sera samples were collec ted, including 27 wild feline sera samples (18 tigers, 8 lions, and 1 jaguar) obtained from Chhatbir zoo, Chandigarh, 42 sera samples (8 tigers, 4 lions and 6 leopards, 2 cheethals, 1 black buck, 12 buffaloes and 9 zoo staff) were received from Jodhpur zoo Rajasthan, 8 sera samples (4 tigers, 3 leopards, 1 lion) from Van Vihar National park, Bohpal, Madhya Pradesh and 3 sera samples (2 lions and 1 tiger) received from Biwani Mini zoo, Haryana, India. The result showed that sera were tested positive by rLigB based LAT, which were reconfirmed using microscopic agglutination test (MAT). The results from LAT were in concordance with MAT. In conclusion, rLigB based LAT is a rapid, pen site, reliable diagnostic tool of high sensitivity and specificity, under laboratory and field conditions, for the detection of Leptospirosis. Asian J. Med. Biol. Res. September 2020, 6(3): 440-448